Sub‐acute hyponatraemia more than chronic hyponatraemia is associated with serious falls and hip fractures. Issue 9 (14th September 2020) - Bhandari, Simran K.; Adams, Annette L.; Li, Bonnie H.; Rhee, Connie M.; Sundar, Shirin; Krasa, Holly; Danforth, Kim N.; Kanter, Michael H.; Kalantar‐Zadeh, Kamyar; Jacobsen, Steven J.; Sim, John J.
Abstract: Background: Falls and hip fractures among older people are associated with high morbidity and mortality. Hyponatraemia may be a risk for falls/hip fractures, but the effect of hyponatraemia duration is not well understood. Aims: To evaluate individuals with periods of sub‐acute and chronic hyponatraemia on subsequent risk for serious falls and/or hip fractures. Methods: Retrospective cohort study in the period 1 January 1998 to 14 June 2016 within an integrated health system of individuals aged ≥55 years with ≥2 outpatient serum sodium measurements. Hyponatraemia was defined as sodium <135 mEq/L with sub‐acute (<30 days) and chronic (≥30 days) analysed as a time‐dependent exposure. Multivariable Cox proportional‐hazards modelling was used to estimate hazard ratios (HR) for serious falls/hip fractures based on sodium category. Results: Among 1 062 647 individuals totalling 9 762 305 sodium measurements, 96 096 serious falls/hip fracture events occurred. Incidence (per‐1000‐person‐years) of serious falls/hip fractures were 11.5, 27.9 and 19.8 for normonatraemia, sub‐acute and chronic hyponatraemia. Any hyponatraemia duration compared to normonatraemia had a serious falls/hip fractures HR (95%CI) of 1.18 (1.15, 1.22), with sub‐acute and chronic hyponatraemia having HR of 1.38 (1.33, 1.42) and 0.91 (0.87, 0.95), respectively. Examined separately, the serious falls HR was 1.37 (1.32, 1.42) and 0.92 (0.88, 0.96) in sub‐acute and chronic hyponatraemia, respectively. Hip fracture HR were 1.52 (1.42, 1.62) and 1.00 (0.92, 1.08) for sub‐acute and chronic hyponatraemia, respectively, compared to normonatraemia. Conclusions: Our findings suggest that early/sub‐acute hyponatraemia appears more vulnerable and associated with serious falls/hip fractures. Whether hyponatraemia is a marker of frailty or a modifiable risk factor for falls remains to be determined.